An analysis of South Africa's food security policy frameworks from a food sovereignty perspective: challenges and implications for genuine long-term food security - Hoepfl, Jason (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2020)
Food price volatility, ecological shocks and unprecedented levels of hunger and obesity are increasing concerns within food security governance, as is the emergence of food sovereignty in broadening critical discussions around food, water, energy and environmental crises. This thesis analyses this changing terrain in the context of South African policy. It analyses shifts in policymaking and the capability of South Africa's food security policy frameworks to include food sovereignty principles and in so doing support genuine long-term food security. A shift in policy priorities from household production, trade and income opportunities towards social safety nets and nutritional interventions is identified. This focus is constrained by an inability to affect structural changes within a deeply inequitable food landscape. An emphasis on commercial farming and unwillingness to challenge large agribusiness, value chains and corporate retail has enabled social differentiation in access to food and the country's colonial land dispensation to continue. Consequently, markets have continued to be antipathetic to the needs of poor producers and consumers in South Africa. To overcome these structural constraints, food security policy needs to be framed within a more radical normative agenda. This is important for challenging inequitable power relations and asserting the social and ecological imperatives of healthy food systems. Food sovereignty has significant potential to support a normative agenda by supporting the multiple farming practices, enterprises and livelihood strategies pursued by poor farmers, the unemployed and working poor whilst preserving sensitive environments for future generations. Determining the future of food security is not the privilege of the few with economic clout or power to govern but the right of all. The incorporation of food sovereignty principles in policymaking is therefore paramount for achieving genuine long-term food security.
Keywords: Food sovereignty -- South Africa; Food security -- South Africa; Food security -- Government policy -- South Africa; Food security -- Climatic factors -- South Africa; Food policy -- Government policy -- South Africa; Agriculture and state -- South Africa; Food industry and trade -- Government policy -- South Africa